Are Informant Reports of Personality More Internally Consistent Than Self Reports of Personality?. (August 2015) - Balsis, Steve; Cooper, Luke D.; Oltmanns, Thomas F.
The present study examined whether informant-reported personality was more or less internally consistent than self-reported personality in an epidemiological community sample ( n = 1, 449). Results indicated that across the 5 NEO (Neuroticism–Extraversion–Openness) personality factors and the 10 personality disorder trait dimensions, informant reports tended to be more internally consistent than self reports, as indicated by equal or higher Cronbach's alpha scores and higher average interitem correlations. In addition, the informant reports collectively outperformed the self reports for predicting responses on a global measure of health, indicating that the informant reports are not only more reliable than self reports, but they can also be useful in predicting an external criterion. Collectively these findings indicate that informant reports tend to have greater internal consistency than self reports.